Randomized, multicenter, parallel, open, phase 4 study to compare the efficacy and safety of rosuvastatin/amlodipine polypill versus atorvastatin/amlodipine polypill in hypertension patient with dyslipidemia - Hae Won Jung; Chang‐Yeon Kim; Seung‐Pyo Hong; Han‐Joon Bae; Ji Yong Choi; Jae Kean Ryu; Jin‐bae Lee; Kyoung‐Hoon Lee; Kyoo‐Rok Han; Dong‐Heon Yang; Chang‐Gyu Park; Gheol‐Woong Yu; et al. (The Journal of Clinical Hypertension, 2023)
Abstract The authors performed this study to investigate the efficacy and safety of a rosuvastatin (RSV)/amlodipine (AML) polypill compared with those of atorvastatin (ATV)/AML polypill. We included 259 patients from 21 institutions in Korea. Patients were randomly assigned to 1 of 3 treatment groups: RSV 10 mg/AML 5 mg, RSV 20 mg/AML 5 mg, or ATV 20 mg /AML 5 mg. The primary endpoint was the efficacy of the RSV 10.20 mg/AML 5 mg via percentage changes in LDL‐C after 8 weeks of treatment, compared with the ATV 20 mg /AML 5 mg. There was a significant difference in the mean percentage change of LDL‐C at 8 weeks between the RSV 10 mg/AML 5 mg and the ATV 20 mg/AML 5 mg (full analysis set [FAS]: −7.08%, 95% CI: −11.79 to −2.38, p = .0034, per‐protocol analysis set [PPS]: −6.97%, 95% CI: −11.76 to −2.19, p = .0046). Also, there was a significant difference in the mean percentage change of LDL‐C at 8 weeks between the RSV 20 mg/AML 5 mg and the ATV 20 mg/AML 5 mg (FAS: −10.13%, 95% CI: −15.41 to −4.84, p = .0002, PPS: −10.96%, 95% CI: −15.98 to −5.93, p < .0001). There was no significant difference in the adverse events rates between RSV 10 mg/AML 5 mg, RSV 20 mg/AML 5 mg, and ATV 20 mg/AML 5 mg. In conclusion, while maintaining safety, RSV 10 mg/AML 5 mg and the RSV 20 mg/AML 5 mg more effectively reduced LDL‐C compared with the ATV 20 mg /AML 5 mg (Clinical trial: NCT03951207).